2015
DOI: 10.1186/s40729-015-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Is the presence of keratinized mucosa associated with periimplant tissue health? A clinical cross-sectional analysis

Abstract: BackgroundLong-term data concerning the impact of missing keratinized mucosa (KM) on periimplant tissue health are rare. The importance of KM for implant success remains unclear.MethodsTwo hundred eleven patients with 967 dental implants were analyzed up to 15 years after implant placement. Implants were divided into two groups: no keratinized mucosa (NKM) and KM. Evaluated parameters were plaque index (mAPI), bleeding index (mSBI), bleeding on probing (BOP), probing depth (PD), width of KM, and radiographic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 37 publications
3
69
0
4
Order By: Relevance
“…Clinical assessments demonstrated that implants with KM < 2 mm exhibited higher mPI and BoP mean values than those with KM ≥ 2 mm both at T0 and T4, in agreement with previous clinical studies (Adibrad et al, ; Bouri et al, ; Chung et al, ; Ladwein et al, ; Souza et al, ). Meta‐analyses from recent systematic reviews (Gobbato, Avila‐Ortiz, Sohrabi, Wang, & Karimbux, ; Lin, Chan, & Wang, ) reported significant differences in plaque control and inflammation, suggesting that KM < 2 mm was associated with more plaque accumulation and peri‐implant tissue inflammation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Clinical assessments demonstrated that implants with KM < 2 mm exhibited higher mPI and BoP mean values than those with KM ≥ 2 mm both at T0 and T4, in agreement with previous clinical studies (Adibrad et al, ; Bouri et al, ; Chung et al, ; Ladwein et al, ; Souza et al, ). Meta‐analyses from recent systematic reviews (Gobbato, Avila‐Ortiz, Sohrabi, Wang, & Karimbux, ; Lin, Chan, & Wang, ) reported significant differences in plaque control and inflammation, suggesting that KM < 2 mm was associated with more plaque accumulation and peri‐implant tissue inflammation.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, others studies in the literature reported no association between KM width and MBL or bone loss around dental implants (Adibrad et al, ; Chung et al, ; Crespi et al, ; Ladwein et al, ; Roccuzzo et al, ). In a study using a sample composed by 967 implants at least 10 years in function, Ladwein et al () evaluated the relationship between KM presence and peri‐implant tissue health, and observed no association between KM width and MBL. However, differently from other studies, the authors conducted MBL measurements on panoramic radiographs, which are less reliable than periapical radiographs.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The AGW in the impaction group was <2 mm, which was reported as the minimal amount required to maintain periodontal health . A deficient AGW may predispose the patient to periodontal inflammation and a subsequent loss of periodontal support, although recent studies suggest that even smaller amounts of KGW and AGW would be sufficient to maintain periodontal health …”
Section: Discussionmentioning
confidence: 96%
“…Often in cases of bone atrophy, keratinized mucosa may not be present, and techniques to increase the amount of keratinized mucosa may be performed during implant installation or second‐stage surgery. The presence of keratinized mucosa has a positive effect on peri‐implant tissue health . In a systematic review, Bassetti et al found that patients with sites with a width of <2 mm of keratinized mucosa developed discomfort during brushing more easily and also exhibited dental plaque accumulation and peri‐implant soft tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%